Accounting for Technical, Ethical, and Political Factors in Priority Setting. Issue 1 (2nd January 2016) - Kieslich, Katharina; Bump, Jesse B.; Norheim, Ole Frithjof; Tantivess, Sripen; Littlejohns, Peter
Abstract : Abstract —This article investigates two cases of priority setting to explore how, in addition to technical considerations, ethical and political factors shape the allocation of health resources. First, we discuss how Thai authorities adjudicated a coverage decision for HLA-B*1502 screening, which meets the national cost-effectiveness threshold for only some of the conditions it can detect. Second, we consider England's Cancer Drugs Fund to investigate the interplay of technical decision making and political reality. Our findings suggest four concluding observations for policy makers and others considering priority-setting processes. First, we observe that different methods can produce conflicting recommendations, which makes priority setting very complex. Second, we suggest that robust processes for generating and weighing political, ethical, and technical evidence are essential because there is no absolute standard by which resource allocation decisions can be made. Third, priority setting is inherently political, and improving its technical and ethical validity means constructing political importance for these other factors. Fourth, we argue that transparency in the trade-offs required to set priorities is important ethically and can help build support politically.